Changes of Volatile Compounds in Table Grapes During Postharvest Storage by SPME Coupled with GC-MS - Zhu, Danshi; Li, Jianrong; Xu, Yongxia; Liu, He; Meng, Xianjun (Asian Journal of Chemistry, 2013)
Volatile compounds of four table grape cultivars, 'Tengnian', 'Longan', 'Cow's Teat' and 'Emerald non-nuclear' were investigated during postharvest storage by SPME/GC-MS. Using the principal component analysis, relations between volatile compounds were associated with cultivars. The results showed that volatile compounds in the four cultivars of table grapes were different and all changed a lot during postharvest storage. Initially a total of 44 volatile compounds, including alcohols, carbonyls, esters and acids, were found in the four cultivars, while only 25 compounds were detected at the end of storage. In addition, the relevant taste indexes total sugar (ºBrix), total acidity (titratable acidity, TA) and sugar acid ratio in different cultivar of grape berry were also determined. It was possible to discriminate the results to monitor the loss of freshness for table grape during storage.